PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR ARTHAGUNA MANDIRI TANGERANG SELATAN - Rizka Wahyuni Amelia; Rodo Marbun, Sopar Togu (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of leadership and work discipline on employee performance at PT. BPR Arthaguna Mandiri in South Tanggerang. The research approach used in this study is the Quantitative Method. The sampling technique used in this study used saturated sampling with a total sample of 75 people. The data collection technique in this study used a questionnaire distributed to employees of PT. BPR Arthaguna Mandiri. Data analysis techniques Data using Descriptive Analysis, Validity Test, Reliability, Simple Regression Analysis, Multiple, Classical Assumptions Test, t-test (Partial), F-test (Simultaneous), Correlation Coefficient and Determination. Processing data in research using SPSS 26. Based on research results the results of multiple linear regression tests obtained the value of the regression coefficient that isY = 23.464 + 0,285X1 + 0,177X2. Simultaneous test results produce a significance value of 0.001 < 0.05 which means Leadership Style and Work Discipline have an effect on Employee Performance. Next, the results of the coefficient of determination show a figure of 0.679 means that 67.9% Leadership Style (X1) and Work Discipline (X2) have an effect on Employee Performance (Y) at PT. BPR Arthaguna Mandiri, while the remaining 32.1% is influenced by variables other interventions. Thus it can be concluded that the hypothesis first (Ha1), second hypothesis (Ha2), and third hypothesis (Ha3) can be accepted.